Pengaruh Self-Improvement dan Self-Determination terhadap Employee Engagement - Setiabudhi; Eva Nur Rahmah; Fahyuni Baharuddin; Prakrisno Satrio; Hayani Hayani (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Employee engagement, also known as employee engagement, is very important for creating a productive work environment and producing high-quality employees. Generation Z employees are looking for opportunities to learn and develop professionally. They also look for opportunities to improve their skills and contribute to their organizations. Technology, flexibility, learning and development, meaning, purpose and purpose are all needs of Gen Z. Generation Z knows how important their work is and the benefits it offers. They also like to work together and work together at work. Employees who are engaged in their work emotionally, cognitively, and physically will be more enthusiastic, committed, and integrated. Two factors that influence employee engagement are self-improvement and self-determination. The research results show that self-determination has a greater influence of 55.2 percent on employee engagement compared to self-improvement (37.4 percent). Apart from that, self-determination and self-improvement have a joint influence of 55.3 percent on employee engagement.